Assessing the cost and utilization of SMS printers by primary health care facilities: lessons learned from South Africa - Naseem Cassim; Floyd Olsen; Lynsey Stewart-Isherwood; Manuel P. da Silva; Wendy S. Stevens (AOSIS, 2023)
Background: Historically, paper-based laboratory reports were delivered by couriers to health facilities resulting in post-analytical delays. As a result, short message service (SMS) printers were deployed to fill this gap, with the global data service platform (GDSP) being primarily used to facilitate deployment. In addition, these printers generate binary and quantitative information that can be used to assess utilization. Objective: The objective of this study was to determine the costs and utilization of the SMS printer program in South Africa. Methods: A cost analysis for 2020 was undertaken. We determined annual equivalent costs (AEC) for staffing, printers, fixed costs related to the national coordinator, consumables, travel costs, database support/hosting/dashboard development, printer repairs, and results transmission. The main outcome of interest was the cost per SMS printer result delivered. Data were extracted to assess utilization as follows: i) months active (based on internet protocol data); ii) signal; iii) battery strength. Results: There were 4,450,116 results delivered to printers that were situated at 2232 primary health care facilities. An AEC of $687,727 was reported, with a cost per result delivered of $0.1618. The SMS printers contributed 73.52% to the total AEC. Overall, 90% of the printers were GDSP based, of which only 69.5% were determined to be active. The majority of active printers reported a signal strength of ≥60% and a battery strength of ≥6 volts. Conclusion: Although the SMS printer program has the potential to reduce post-analytical delays, pathology services should migrate to an end-to-end electronic interface to improve patient care.